If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 = 84 + -7x Reorder the terms: 6 + 3x = 84 + -7x Solving 6 + 3x = 84 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 6 + 3x + 7x = 84 + -7x + 7x Combine like terms: 3x + 7x = 10x 6 + 10x = 84 + -7x + 7x Combine like terms: -7x + 7x = 0 6 + 10x = 84 + 0 6 + 10x = 84 Add '-6' to each side of the equation. 6 + -6 + 10x = 84 + -6 Combine like terms: 6 + -6 = 0 0 + 10x = 84 + -6 10x = 84 + -6 Combine like terms: 84 + -6 = 78 10x = 78 Divide each side by '10'. x = 7.8 Simplifying x = 7.8
| 27x^3-7=0 | | (6x-7)(x-8)=(x+40)(1-2x) | | 4v^2-49t^2=0 | | 2x+3x+4x-5=2+3+4x | | (5x+6)(x+6)=(x+10)(4x+3) | | n-10=0.5n-7 | | 36r^2+60rg+25g^2=0 | | -3=6-q/9 | | 4(3x+4)=4x+8 | | n-10=0.5-7 | | 17x=0.005 | | 3x-7=5-6x | | 25m^2-30m+9=0 | | (x-1)(x-2)=(x-5)(x+1) | | 6-2x=5x+10 | | 8-2x=3x+8 | | g(3)=1.67 | | 6x+7y=49 | | 9x-9=9(x+9) | | 17x=1.9 | | 576=10x-0.04x^2 | | -3x-9=3x-3 | | y=x^2+6x+18 | | -25=5(3q-2) | | 3.6x=2.1x+10.5 | | 8-h=12 | | 8-5= | | 0.95y+1=y-0.5 | | 3x-15=59 | | 4x+8=10x-10 | | 4-8d=16 | | 5x^4+13x^2-6=0 |